Contribution of hypoxia inducible factor-1 during viral infections - Antonia Reyes (Taylor & Francis Group, 2020)
Hypoxia-inducible factor 1 (HIF-1) is a transcription factor that plays critical roles during the cellular response to hypoxia. Under normoxic conditions, its function is tightly regulated by the degradation of its alpha subunit (HIF-1α), which impairs the formation of an active heterodimer in the nucleus that otherwise regulates the expression of numerous genes. Importantly, HIF-1 participates in both cancer and infectious diseases unveiling new therapeutic targets for those ailments. Here, we discuss aspects related to the activation of HIF-1, the effects of this transcription factor over immune system components, as well as the involvement of HIF-1 activity in response to viral infections in humans. Although HIF-1 is currently being assessed in numerous clinical settings as a potential therapy for different diseases, up to date, there are no clinical studies evaluating the pharmacological modulation of this transcription factor as a possible new antiviral treatment. However, based on the available evidence, clinical trials targeting this molecule are likely to occur soon. In this review we discuss the role of HIF-1 in viral immunity, the modulation of HIF-1 by different types of viruses, as well as the effects of HIF-1 over their life cycle and the potential use of HIF-1 as a new target for the treatment of viral infections.